Expedient Treatment of a Collodion Baby - Michael Chung; Jaime Pittenger; Stuart Tobin; Andrew Chung; Nirmala Desai (Case Reports in Dermatological Medicine)
Only ~270 cases of collodion babies have been reported in the literature since 1892. As the name suggests, the term “collodion baby” refers to a phenotype that can be characterized by a yellow, shiny, tight parchment-like membrane stretched over the skin. Although the collodion membrane is only an evanescent condition of the newborn, neonatal complications can occur in 45% of all collodion babies, leading to a mortality rate of ~11% in the first few weeks of life. Most children born as collodion babies will spontaneously desquamate within 2 weeks, but may be as long as 3 months. Eventually, these children develop signs of one of several types of ichthyosis, which gives the skin the appearance of “fish scales.” We report a unique case of a Caucasian male that was born as a Collodion baby at the University of Kentucky Children's Hospital in Lexington, Kentucky. Although the impairment of the skin barrier function put the patient at risk for a number of complications, he improved significantly after being treated with emollients and antibiotics. In contrast to previous findings, we found that skin emollients were beneficial and did not increase the risk of infection.